Mongolia Quarterly Economic Update, February 2012 - World Bank (Washington, DC, 2017)
Gross Domestic Product (GDP) growth accelerated to an unprecedented 17.3 percent in 2011 from 6.4 percent in 2010 and the unemployment rate fell from 13 percent in 2010 to 9 percent in 2011. However, real wages for unskilled workers in the urban informal sector are starting to fall as the inflation rate reached 11.1 percent year-on-year in December. Sharply rising government spending is the root cause of overheating: government spending rose by 56 percent in 2011 and is budgeted to rise by a further 32 percent this year, fueled by sharply rising resource revenues. This pro-cyclical fiscal policy could result in another 'boom-and-bust' cycle Mongolia experienced before, particularly as the global economy could face a substantial slowdown in growth due to the continuing European sovereign debt crisis, and which could result in a sharp drop in mineral prices and subsequently government revenues There have been major legislative developments in 2011 and early 2012 aimed at strengthening policy institutions and frameworks. The Integrated Budget Law (IBL) was passed in December 2011: this organic budget law contains measures to support fiscal sustainability and the successful implementation of the Fiscal Stability Law. It also strengthens the public investment framework by requiring feasibility studies and alignment with national priorities for projects to be included in the Public Investment Program and the budget. The Social Welfare Law was passed in early January. This mandates the provision of a targeted poverty benefit replacing the existing system of universal cash transfers. To ensure macroeconomic stability and to prevent a hard landing for the economy in case of an adverse external shock, Mongolia needs to adhere strictly to prudent fiscal policies as set out in the FSL and IBL and tightening both fiscal and monetary policy to reduce inflation, take macro-prudential action to reduce systemic risks in the banking sector and maintain a flexible exchange rate that will act as the first buffer in any external shock materializes. These are uncertain times for Mongolia. The economy faces growing headwinds from the global economic environment, while the looming elections increase domestic uncertainty. Until a substantial amount of savings has accumulated in the stabilization fund, Mongolia remains strongly exposed to volatility in commodity prices.